A new fossil soldier beetle (Coleoptera: Cantharidae: Malthininae) from Baltic amber - Fanti, Fabrizio; Sontag, Elżbieta (Zootaxa, 2019)
The very abundant representatives of the genus Malthodes Kiesenwetter, 1852 from the Eocene amber forests show a remarkable diversity of body forms, especially regarding the last abdominal segments, both tergites and sternites. These structures are important during the mating. In the present work, we describe a new species, Malthodes gedanicus sp. nov. characterized by the last sternite elongated and apically divided into two long and flat squarish lobes with three tips of which the central is longest, and by the last tergite elongated and spatuliform apically. The phylogenetic relationships based only on the shape of the last abdominal segments remain unclear and the new species is very vaguely similar to M. trifurcatus Kiesenwetter, 1852.